Cardiovascular risk estimation with 5 different algorithms before and after 5 years of bDMARD treatment in rheumatoid arthritis - Cacciapaglia, Fabio; Fornaro, Marco; Venerito, Vincenzo; Perniola, Simone; Urso, Livio; Iannone, Florenzo (European journal of clinical investigation, 2020)
Background Assessing cardiovascular (CV) risk represents a challenge for clinicians because more variables can impact CV risk. The aim of this study was to evaluate the change of CV risk after 5 years of biological treatment in rheumatoid arthritis (RA) patients and impact of prolonged low disease activity on 5 different CV risk algorithms. Materials and methods We estimated the CV risk, at baseline and at 5‐year follow‐up (FU), with the Systematic COronary Risk Evaluation(SCORE) charts, the algorithm ‘Progetto Cuore’, the QRISK3‐2018 score, the Reynold Risk Score(RRS) and the Expanded Risk Score in RA(ERS‐RA). Clinical disease activity index(CDAI) was used to define RA activity. Wilcoxon signed‐rank test was used to compare CV risk scores. Results In 110 patients with a 5‐year FU on biological disease‐modifying anti‐rheumatic drug treatment, we observed an increase in the 10‐year CV risk estimated by SCORE charts [from mean (SD) 0.9% (1.4) to 1.1% (1.5), P < .001], ‘Progetto Cuore’ [from mean (SD) 5.5% (7.2) to 6.2% (6.8), P < .001], QRISK3‐2018 [from mean (SD) 9.3% (10.1) to 11.9% (10.8), P < .001) and RRS [from mean (SD) 5.6% (6.4) to 6.2% (7.5), P < .05], mainly due to age raise. ERS‐RA highlighted a significant decrease of estimated CV risk in patients with persistent CDAI ≤ 10[from mean (SD) 9.6% (11.2) to 7.3% (6.4), P < .05], despite age increase and its impact on the CV risk score. Conclusions Algorithms commonly used to estimate 10‐year CV risk in RA perform differently. Scores that include specific inflammatory RA‐related variables seem to decrease with amelioration of disease activity. Further investigations are warranted to explore the predictive value of their changing over time.